The relationship between physical performance measures, bone mineral density, falls, and the risk of peripheral fracture: a cross-sectional analysis - Bennani Loubna; Allali Fadoua; Khazzani Hamza; Ichchou Linda; El Mansouri Laila; Abourazzak Fatima E; Abouqal Redouane; Hajjaj-Hassouni Najia (BMC Public Health, 2009)
Abstract Background Several factors, in addition to low bone mineral density (BMD), have been identified as risks for fractures, including reduced levels of physical activity, poor balance and low physical performance. The aim of this study was to evaluate the relationship between physical performance measures, BMD, falls, and the risk of peripheral fracture in a population sample of Moroccan women. Methods 484 healthy women were included. Three measures were used to assess physical performance: timed get-up-and-go test 'TGUGT', five-times-sit-to-stand test '5 TSTS' and 8-feet timed walk '8 FTW'. The association between physical performance measures and BMD, peripheral fracture and falls was performed by univariate and multivariate analysis. Results The mean age was 55.1 years. Higher 'TGUGT', '5 TSTS', '8 FTW' test scores were associated with lower BMD measured at different sites (p range from < 0.001 to 0.005). The relationship between the three tests and BMD in all measured sites remained significant after multiple linear regression (p range from <0.001 to 0.026). In the group of post-menopausal patients, the scores of 'TGUGT' and '8 FTW' were significantly higher in fractured patients compared with patients without. After logistic regression, a score of 'TGUGT' > 14.2 sec, a score of '5 TSTS' > 12.9 sec and a score of '8 FTW' > 4.6 sec respectively, increased the probability of anterior peripheral fracture by 2.7, 2.2 and 2.3 (OR = 2.7; 95% CI = 1.2–6.4, OR = 2.2; 95% CI = 1.1–5.2; and OR = 2.3; 95% CI = 1.1–5.1). There was a significant positive correlation between the number of fall/year and the 3 tests. This correlation persisted after poisson regression. Conclusion This study suggested that low physical performance is associated with low BMD, and a high risk of history of falls and fractures.